Ato ni Bai exploring the future of durian fruit agritourism through a postharvest research complex - Nierre, Jieson N. (College of Architecture, University of the Philippines Diliman, 2025)
A project contributing to the favorable progress of the Philippine durian industry and its current industrial success brought about issues regarding the unpreparedness of Filipino producers in regard to production volume and quality, exposing multifaceted faults from comparatively primitive farming techniques to barely functioning postharvest facilities. A constructivist approach in examining the different experiences and problems of stakeholders in the industry was utilized, strengthened by qualitative data gathering through direct interviews and precedent visits. The design proposal aims to develop a fully functional postharvest research center, highlighting the importance of knowledge exchange as an integral part of research, equipped with an extension and institution cooperation facility containing a production warehouse reserved for the facility's own processing or for the use of small-scale farmers, traders, exporters, and processors, ameliorating the smaller integral stakeholders of the industry while serving as a symbol for the Philippines' durian agritourism through a production-oriented approach delivering the services that are typically done in between the farm-to-table experience. Backed up by intensive architectural translations, the intricacies of a postharvest research complex were explored to uncover the inherent properties of agritourism.